Predicting the effects of winter water warming in artificial lakes on zooplankton and its environment using combined machine learning models - Kruk, Marek; Goździejewska, Anna Maria; Artiemjew, Piotr (Scientific reports, 2022)
This work deals with the consequences of climate warming on aquatic ecosystems. The study determined the effects of increased water temperatures in artificial lakes during winter on predicting changes in the biomass of zooplankton taxa and their environment. We applied an innovative approach to investigate the effects of winter warming on zooplankton and physico-chemical factors. We used a modelling scheme combining hierarchical clustering, eXtreme Gradient Boosting (XGBoost) and SHapley Additive exPlanations (SHAP) algorithms. Under the influence of increased water temperatures in winter, weight- and frequency-dominant Crustacea taxa such as Daphnia cucullata , Cyclops vicinus , Cryptocyclops bicolor , copepodites and nauplii, and the Rotifera: Polyarthra longiremis , Trichocerca pusilla , Keratella quadrata , Asplanchna priodonta and Synchaeta spp. tend to decrease their biomass. Under the same conditions, Rotifera: Lecane spp., Monommata maculata , Testudinella patina , Notholca squamula , Colurella colurus , Trichocerca intermedia and the protozoan species Centropyxis acuelata and Arcella discoides with lower size and abundance responded with an increase in biomass. Decreases in chlorophyll a, suspended solids and total nitrogen were predicted due to winter warming. Machine learning ensemble models used in innovative ways can contribute to the research utility of studies on the response of ecological units to environmental change.